Numerical Solutions of Some Parabolic Partial Differential Equations Using Finite Difference Methods - Singla, Rishu; Jiwari, Ram (Guide) (My University, 2012)
In this thesis an attempt has been made to solve some parabolic partial differential equations by using finite differences methods.
M.Sc. (Mathematics and Computing)
Keywords: Parabolic Partial Differential Equations; Burger's Equation